Purification, crystallization and preliminary X-ray analysis of Triatoma virus (TrV) from Triatoma infestans - Rozas Dennis, Gabriela Susana (2004)
Triatoma virus (TrV) is a viral pathogen of the blood-sucking reduviid bug Triatoma infestans, the most important vector of American human trypanosomiasis (Chagas' disease). TrV has been putatively classified as a member of the Cripavirus genus (type cricket paralysis virus) in the Dicistroviridae family. This work describes the purification of TrV particles from infected T. infestans and their crystallization and preliminary crystallographic analyses. Two different crystal forms, rhombohedral and orthorhombic, were obtained at room temperature by the hanging-drop vapour-diffusion technique using polyethylene glycol and polyethylene glycol monomethylether as precipitants. The rhombohedral crystals have unit-cell parameters a = b = 306.6, c = 788.4 Å (hexagonal setting), diffract to 3.2 Å resolution and contain one-third of the viral particle per asymmetric unit. The orthorhombic crystals have cell parameters a = 336, b = 351, c = 332 Å, diffract to about 2.5 Å resolution, and contain one-half of a virus particle in the asymmetric unit. A complete diffraction data set has been collected to 3.2 Å resolution, using synchrotron radiation, from a single rhombohedral crystal under cryogenic conditions. © 2004 International Union of Crystallography.